Analysis and Design of Anosmia Disease Diagnosis Expert System Using Forward Chaining and Certainty Factor Methods - Deosa Putra Caniago; M. Abrar Masril (IJISTECH (International Journal of Information System and Technology), 2022)
The nose is an important organ for the body as the five human senses, disorders often occur in the nasal organs, one of which is anosmia disease, ansomia is a disorder that occurs in the nasal organs that can eliminate the sufferer's ability to feel smells, basically anosmia is common, but in the midst of a serious pandemic. With research on Expert Systems using the Forward Chaining and Certainty Factor methods so that users can consult the system like consulting an ENT-KL specialist doctor with an accuracy of 96%